2010
DOI: 10.1002/lt.21995
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to prevent recurrent portal vein stenosis following interventional radiology in pediatric liver transplantation

Abstract: Portal vein complications after liver transplantation (LT) are serious complications that can lead to graft liver failure. Although the treatment of interventional radiology (IVR) by means of balloon dilatation for portal vein stenosis (PVS) after LT is an effective method, the high rate of recurrent PVS is an agonizing problem. Anticoagulant therapy for PVS is an important factor for preventing short-term recurrence following IVR, but no established regimen has been reported for the prevention of recurrent PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…Shibata et al [128] (2005) reported the most important series in the literature where the recurrence rate was 28.6%. Some authors recommend the use of anticoagulant therapy for the prevention of recurrent PVT [134] . Recently, Sanada et al [134] (2010) concluded that the use of three anticoagulant therapies, i.e., lowmolecularweight heparin, warfarin and aspirin, significantly reduced the recurrence of thrombosis with a median followup of three months [134] .…”
Section: Summary Of the Clinical Characteristics About Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shibata et al [128] (2005) reported the most important series in the literature where the recurrence rate was 28.6%. Some authors recommend the use of anticoagulant therapy for the prevention of recurrent PVT [134] . Recently, Sanada et al [134] (2010) concluded that the use of three anticoagulant therapies, i.e., lowmolecularweight heparin, warfarin and aspirin, significantly reduced the recurrence of thrombosis with a median followup of three months [134] .…”
Section: Summary Of the Clinical Characteristics About Pvsmentioning
confidence: 99%
“…Some authors recommend the use of anticoagulant therapy for the prevention of recurrent PVT [134] . Recently, Sanada et al [134] (2010) concluded that the use of three anticoagulant therapies, i.e., lowmolecularweight heparin, warfarin and aspirin, significantly reduced the recurrence of thrombosis with a median followup of three months [134] . Additionally, some authors have coupled endovascular treatment with surgical PV access [106] .…”
Section: Summary Of the Clinical Characteristics About Pvsmentioning
confidence: 99%
“…3,4,5). Imaging performed immediately after angioplasty documented the partial success of the procedure with persistence of reverse flow in the splenic vein.…”
Section: Casementioning
confidence: 99%
“…Patency of the vascular reconstructions is a key factor in the success of LT [3], and complications of the portal anastomotic stenosis may cause the failure of surgery [4]. The disproportion in vessel calibre between adult donor and recipient, tension and torsion of the anastomosis (sometimes treated with surgical patches) are the main causes of early or late portal stenosis [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation